Classification of Muslim Woman Student Using Artificial neural network - Ulil Albab; Imam Much Ibnu Subroto; Muhammad Haddin (Universitas Islam Sultan Agung, 2020)
Hijab is a female genital covering commonly used by adult women. The number of hijab wearing fashion modes is developing, this makes one of the factors lack of understanding about using the correct hijab. By utilizing image processing using classification techniques can be distinguished between veiled women and not veiled. Artificial Neural Network (ANN) is an artificial intelligence that presents like a human brain by means of learning. ANN can be embedded into a computer program for the calculation process. One of the uses of ANN is to process the image to be classified. Image processing stages are data acquisition, preprocessing, edge detection, training, testing and classification. Based on the tests that have been carried out as many as 20 experiments, the results of image classification using Artificial Neural Network algorithm and backpropagation learning methods show a good level of accuracy.